A Semantic Analysis of Lexical Ambiguity in English Online News Headlines - Leony Elisabeth S; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines lexical ambiguity in English news headlines published in online media, focusing on how ambiguous word choices may lead to different interpretations among readers. Lexical ambiguity occurs when a single word has more than one meaning, especially in context-limited texts such as headlines. The data for this study consist of eight selected headlines taken from The Jakarta Post and BBC News. This study employs a qualitative descriptive method to identify ambiguous words and analyze their possible meanings based on semantic theory. The findings reveal that all selected headlines contain lexical ambiguity, particularly in words such as following, race, summons, post, looms, hears, spike, and alarm. These ambiguities mainly arise due to polysemy and the limited context in headlines. While lexical ambiguity can make headlines more engaging and attention-grabbing, it may also lead to misinterpretation. Therefore, this study emphasizes the importance of understanding lexical ambiguity in order to interpret news headlines more accurately.